AUTOMATIC DETECTION AND MONITORING OF AMMONIA (NH3) CONCENTRATION IN WASTEWATER - Salohiddinov Fayzulloh Fazliddin o’g’li (European Science Publishing, 2024)
This article explores the innovative approach of automatic detection and monitoring systems for ammonia (NH3) concentration in wastewater. Traditional methods of monitoring NH3 pollution are labor-intensive and lack real-time data, leading to inefficient resource allocation and potential environmental hazards. However, recent advancements in technology have introduced automatic monitoring systems that offer real-time data insights, enabling proactive intervention and informed decision-making. This article discusses the principles, components, implementation, case studies, regulatory compliance, and future trends of automatic monitoring systems, highlighting their transformative potential in environmental management practices.
Keywords: ammonia concentration, wastewater, automatic detection, monitoring systems, environmental management, real-time data, regulatory compliance, sustainability.